Análisis de género en la carrera judicial y en el acceso a las altas corporaciones nacionales de la justicia en Colombia. Estado del arte. (2007)
The analysis of gender in the judicial career and in the access to high positions in the national justice corporations in Colombia, requires the examination of some research, studies and reports related to the right to equality, the guarantee of no discrimination and the introduction of the gender perspective.These studies have been developed by the academy, researchers, governmental and non-governmental organizations in the national and international scene, in Latin America and the Caribbean. The objectiveis to provide theoretical elements for research as well as for the analysis of contents and statistical data, especially those referring to the access of women as users of the justice service and theirentrance to the justice administration as judges and high court judges.